Genetic Variability and Genotypic, Phenotypic Correlation Studies for Yield and Related Traits In Single Cross Hybrids of Maize (Zea Mays L.) - Mohammed, Mohammed O. (Science Journal of University of Zakho, 2014)
The study was connected to evaluate seven mays hybrids for genetic variability for yield components at Faculty of Agriculture and forestry field university of Duhok during spring 2011 and 2012 .The result show highly significant different between the genotype for plant height, leaf area , and significant at 0.05 level for ear height ,number. of grain ear-1 and non-significant for 300-grain weight and grain yield plant-1 in spring 2011. While the main square for genotype was highly significant for leaf area and significant for plant height, ear height ,number of row ear-1,and non-significant for rest characters ,also show significant effect between hybrid and yield. Plant height exhibited significant positive genotypic correlation with ear height, leaf area ,300-grain weight ,and not significant with yield plant-1 while the phenotypic correlation show appositive non significant correlation between number of row with leaf area with (rph =0.60).